2020
DOI: 10.1063/5.0023902
|View full text |Cite
|
Sign up to set email alerts
|

Electronic-ionic coupling in perovskite based solar cells: Implications for device stability

Abstract: Ion migration into blocking layers toward the metallic electrodes is studied within a semiconductor device model framework. We find that ion leakage into the blocking layers and their accumulation at the electrode interface are significantly affected by the electronic injection barrier at the contact. Specifically, we find that if the device structure promotes, under light, hole (electron) accumulation within the perovskite layer, these excess holes (electrons) would release an almost equivalent number of cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In a recent publication we showed that when operated close to the maximum power point the injection barrier at the contacts also plays a role. 35 However, since we deal here with zero bias and zero light (zero current) the injection barriers were found to have no effect (not shown). To place the simulations on solid ground we chose to perform them under experimental conditions similar to those reported by Galatopoulos et al 18 4 shows that at the point where the density at the contact of the 50 nm BL reached 90% of its final value, nothing is observed at the contact of the 200 nm one.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a recent publication we showed that when operated close to the maximum power point the injection barrier at the contacts also plays a role. 35 However, since we deal here with zero bias and zero light (zero current) the injection barriers were found to have no effect (not shown). To place the simulations on solid ground we chose to perform them under experimental conditions similar to those reported by Galatopoulos et al 18 4 shows that at the point where the density at the contact of the 50 nm BL reached 90% of its final value, nothing is observed at the contact of the 200 nm one.…”
Section: Discussionmentioning
confidence: 91%
“…18,19,34 Hence, while most simulation results, today, contain the ''hidden'' assumption that the electron/hole blocking layers also function as ion blocking, we will examine the effect of ion migration into the electron/hole blocking layers. 35 This work was primarily inspired by Rivkin et al 19 who quantified the anion density within the hole blocking layer (HBL) and by Galatopoulos et al 18 which showed that the HBL may function as an ion blocking layer (IBL) too. Hence, while in ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Extensive studies have been performed to investigate the properties of the ions, [25,26] the ion distribution in PSCs under dark and illumination, [27] and the electronic-ionic coupling and its impact on device operation. [28] PSCs differ from PeLEDs in that the fabrication of PeLEDs typically involves the use of largely excess organic halide salts; a portion of these halides do not participate in the perovskite lattice but instead reside on the surfaces and grain boundaries, thus inducing additional mobile ions in the PeLEDs. [29][30][31] More importantly, the electric field across the very thin perovskite layer (typically tens of nanometers) in a PeLED is much stronger than the field in a PSC.…”
mentioning
confidence: 99%
“…Since the groundbreaking studies demonstrating the potential of perovskite materials for photovoltaics, the field has advanced rapidly with current record efficiencies exceeding 25% within less than a decade . Besides the efficiency benchmarking, there have also been advances in understanding the chemistry, physics, and device chemical physics of these cells both from a theoretical and experimental side. The grain-scale microstructure of perovskite thin films has also been studied and optimized, with particular attention on increasing the average grain size , but with little focus on the influence of the distribution of sizes.…”
mentioning
confidence: 99%